Effect of goal-directed mobilisation versus standard care on physical functioning among medical inpatients: the GoMob-in randomised, controlled trial - Christine Baumgartner; Andreas Limacher; Drahomir Aujesky; Martin Verra; Carole E Aubert; Fabian D Liechti; Maria M Wertli; Jean-Benoît Rossel; Jeannelle Heinzmann; Joachim M Schmidt Leuenberger; Nina A Schmutz; Michael L Rossen (BMJ Open)
Objective To assess the effect of goal-directed mobilisation (GDM) on physical functioning in medical inpatients.Design Randomised, controlled, single-centre, parallel, superiority trial with a 3-month follow-up and blinded outcome assessment.Setting General internal medicine wards of a Swiss tertiary acute hospital, September 2021 to April 2023.Participants Adults with expected hospitalisation of ≥5 days, physiotherapy prescription and ability to follow study procedures.Intervention GDM during hospitalisation, which includes personal goal setting and a short session of patient education through a physiotherapist (experimental group), versus standard care (control group).Outcome measures The primary outcome was the change in physical activity between baseline and day 5 (De Morton Mobility Index (DEMMI)). Secondary outcomes included in-hospital accelerometer-measured mobilisation time; in-hospital falls; delirium; length of stay; change in independence in activities of daily living, concerns of falling and quality of life; falls, readmission and mortality within 3 months.Results The study was completed by 123 of 162 (76%) patients enrolled, with the primary outcome collected at day 5 in 126 (78%) participants. DEMMI Score improved by 8.2 (SD 15.1) points in the control group and 9.4 (SD 14.2) in the intervention group, with a mean difference of 0.3 (adjusted for the stratification factors age and initial DEMMI Score, 95% CI −4.1 to 4.8, p=0.88). We did not observe a statistically significant difference in effects of the interventions on any secondary outcome.Conclusions The patient’s physical functioning improved during hospitalisation, but the improvement was similar for GDM and standard of care. Improving physical activity during an acute medical hospitalisation remains challenging. Future interventions should target additional barriers that can be implemented without augmenting resources.Trial registration number NCT04760392.